Deficiência intelectual: o que os graduandos das licenciaturas sabem a respeito? - Lira, Nicolle Lenharo [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
Inclusion is a topic that is much discussed today reaching various aspects and areas of human social life. School inclusion is understood as essential for the development of society and within this,inclusion encompasses several types of individuals with their characteristics and peculiarities. The inclusion of the student with Intellectual Disability (DI) is strictly linked to teacher training and its ideology about inclusion. The preparation and integration of this new teachers (of common class) with the specialized teacher will directly influence in the development and the acquisition of the knowledge of this student, therefore, the objective of the research was to analyze the knowledge that undergraduate students of Unesp de Bauru have on intellectual disability. The data collection was done through a digital form, which contained alternative and dissertative questions. The data were systematized from the qualitative approach and it was based on the hypothesis that the training of the future teachers in relation to the inclusion needs to be deepened, providing security to him when he is in contact with a student with ID. The results allowed confirming the need for reassessment of the discipline that deals with this subject, enabling the professionals of the education to deepen on how to work with these students promoting the inclusion so that there is a teaching of better quality

A inclusão é um tema muito discutido na atualidade, atingindo diversos aspectos e áreas da vida social humana. A inclusão escolar é entendida como essencial para o desenvolvimento da sociedade, e dentro desta inclusão abrange-se diversos tipos de indivíduos com suas características e peculiaridades. A inclusão do aluno com Deficiência Intelectual (DI) está estritamente ligada com a formação do docente e com sua ideologia sobre a inclusão. O preparo e a integração deste professor (de classe comum) com o docente especializado influenciará diretamente no desenvolvimento e na aquisição do saber deste aluno, por isso, o objetivo da pesquisa foi analisar o conhecimento que graduandos de licenciatura da Unesp de Bauru possuem sobre deficiência intelectual. A coleta dos dados realizou-se por meio de um formulário digital, o qual continha questões alternativas e dissertativas. Os dados foram sistematizados a partir da abordagem qualitativa e partiu-se da hipótese de que a formação dos futuros docentes em relação à inclusão precisa ser aprofundada, proporcionando segurança á ele, quando este estiver em contato com um aluno com DI. Os resultados permitiram confirmar a necessidade de reavaliação da disciplina que aborda tal assunto, possibilitando aos profissionais da educação aprofundamento sobre como trabalhar com estes alunos promovendo a inclusão para que haja um ensino de melhor qualidade
Keywords: Incapacidade intelectual; Professores - Formação; Educação inclusiva; Education